Mountain & Alpine Medicine - Berger MM; Schiefer LM; Treff G; Sareban M; Swenson ER; Bärtsch P (Dynamic Media Sales Verlag, 2020)
The interest in trekking and mountaineering is increasing, and growing numbers of individuals are travelling to high altitude. Following ascent to high altitude, individuals are at risk of developing one of the three forms of acute high-altitude illness: acute mountain sickness (AMS), high-altitude cerebral edema (HACE), and high-altitude pulmonary edema (HAPE). The cardinal symptom of AMS is headache that occurs with an increase in altitude. Additional symptoms are anorexia, nausea, vomiting, dizziness, and fatigue. HACE is characterized by truncal ataxia and decreased consciousness that generally but not always are preceded by worsening AMS. The typical features of HAPE are a loss of stamina, dyspnea, and dry cough on exertion, followed by dyspnea at rest, rales, cyanosis, cough, and pink, frothy sputum. These diseases can develop at any time from several hours to 5 days following ascent to altitudes above 2,500-3,000 m. Whereas AMS is usually self-limited, HACE and HAPE represent life-threatening emergencies that require timely intervention. For each disease, we review the clinical features, epidemiology and the current understanding of their pathophysiology. We then review the primary pharmacological and non-pharmacological approaches to the management of each form of acute altitude illness and provide practical recommendations for both prevention and treatment. The essential principles for advising travellers prior to high-altitude exposure are summarized.Key Words: Acute Mountain Sickness, High Altitude Cerebral Edema, High Altitude Pulmonary Edema, Hypoxia